Research on Ev-Do Multi-Carrier Coverage Consistency Control - Baofa Hu; Minghui Lin; Wen Chen (Dianxin kexue, 2015)
In the crowded area，China Telecom cdma2000 Ev-Do sector is configured with multi-carrier for improving the capacity.Nevertheless，the users’ experience is influenced because of the carrier’s effective coverage difference.Meanwhile，the traditional optimization methods for multi-carrier coverage such as performance index analysis and drive test are time-consuming and costly.According to the multi-carrier wireless environment typical model and combining with the DRC and call data analysis，an effective method to control the coverage of each carrier was proposed.This method can improve the optimization efficiency of China Telecom cdma2000 network by transforming the empirical method into quantitative strategy.